2014
DOI: 10.1002/2013wr015065
|View full text |Cite
|
Sign up to set email alerts
|

Single‐parameter model of vegetated aquatic flows

Abstract: Coupled flows through and over permeable layers occur in a variety of natural phenomena including turbulent flows over submerged vegetation. In this work, we employ a two-domain approach to model flow through and over submerged canopies. The model, amenable of a closed-form solution, couples the log-law and the Darcy-Brinkman equation, and is characterized by a novel representation of the drag force which does not rely on a parametrization through an unknown drag coefficient. This approach limits to one, i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 36 publications
1
50
0
Order By: Relevance
“…Here we use the flow model proposed by Battiato [] and Battiato and Rubol [] as the analytical approximation of the mean velocity profile above and within the obstruction. In the following, we provide the flow model description for completeness.…”
Section: Turbulent Flow Over a Permeable Layermentioning
confidence: 99%
See 2 more Smart Citations
“…Here we use the flow model proposed by Battiato [] and Battiato and Rubol [] as the analytical approximation of the mean velocity profile above and within the obstruction. In the following, we provide the flow model description for completeness.…”
Section: Turbulent Flow Over a Permeable Layermentioning
confidence: 99%
“…The methodology is appealing since it is flexible and computationally inexpensive in comparison to existing numerical models. The velocity profile we adopt is based on the two‐domain model proposed by Battiato and Rubol []. The proposed flow model treats the canopy layer as a porous medium [see Lowe et al ., ; Papke and Battiato , ; Battiato and Rubol , ] and is coupled to the advection‐dispersion equation with spatially variable coefficients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a number of studies have experimentally or analytically demonstrated the impact of morphological and topological alteration on, e.g., solute dispersion and fouling at the system (macro-) scale (Maruf et al 2013b;Battiato et al 2010;Griffiths et al 2013;Battiato & Rubol 2014;Rubol et al 2016;Ling et al 2016Ling et al , 2018, ROMs systems are still primarily optimized by trail and error. This is due to the lack of quantitative understanding of the impact of morphological and/or topological modifications on membrane fouling at prescribed operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Emergent and submerged vegetation also affects solute transport by altering the distribution of the velocity and the mixing coefficient in the channel [Nepf, 2012;Shucksmith et al, 2010;Musner et al, 2014]. Battiato and Rubol [2014] and Rubol et al [2016] used a two-domain approach to model flow through and over submerged canopies, and derived a semianalytical solution for the concentration field in submerged vegetated systems under steady-state conditions. Day [1975] analyzed the behavior of the first two moments of the breakthrough curves from an extensive series of tracer experiments in small mountain streams and showed that the standard deviation of an initially concentrated mass increases linearly with distance instead of its square root, in contrast with Taylor's mixing model.…”
Section: Introductionmentioning
confidence: 99%